Plastic Waste Management Through Mobile Application - Shukla, Omnarayan (Journal of Advanced Research in Glass, Leather and Plastic Technology; Vol 3 No 1 (2020): Journal of Advanced Research in Glass, Leather & Plastic Technology, 2021)
Reusing plastic is one of the various ground-breaking techniques for diminishing the carbon impression of the planet. However, most by far of the plastic waste in Mumbai ends up in the dumping yards and expended nearby the other garbage, as opposed to getting reused. 3.5 immense measures of plastic is as such sent in the city's air as hazardous gases. Plastic waste is a general issue-cause air contamination, water debasement, etc. The genuine purpose behind this is the weakness of the close by government body to segregate plastic waste from other garbage. The harmful effects of inefficient plastic exchange, its causes and the peril it positions to Mumbai are by and large minded in this paper. The Store Markdown structure using sharp reject containers can beat this issue by detaching plastic from other waste for reusing. To complete the structure, normalized distinguishing proof inspecting advancement is used to store a charge while buying a plastic thing and a normalized recognizable proof scanner at the sagacious can checks the normalized ID for limiting the cost to the customer. Nearby a relevant examination of the feasibility of a similar system that was executed by the Zero Waste Scotland commission, we in like manner close the ideal conditions and burdens of the structure. How to cite this article: Shukla O, Singh SS. Plastic Waste Management Through Mobile Application. J Adv Res Glass Leath Plast Tech 2020; 3(1): 14-17.